2021
DOI: 10.3390/ijerph18136804
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders, Pain Medication, and in-Hospital Mortality among Patients with COVID-19 in South Korea: A Population-Based Cohort Study

Abstract: We aimed to investigate whether comorbid musculoskeletal disorders (MSD)s and pain medication use was associated with in-hospital mortality among patients with coronavirus disease 2019 (COVID-19). Adult patients (≥20 years old) with a positive COVID-19 diagnosis until 5 June 2020 were included in this study, based on the National Health Insurance COVID-19 database in South Korea. MSDs included osteoarthritis, neck pain, lower back pain, rheumatoid arthritis, and others, while pain medication included paracetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Twenty literature reviews were identified2, 12-30 . Of the remaining studies, 31 presented original research 31-61 , 6 were case series 62-67 , 24 were case reports 68-91 , 1 provided a specialist’s opinion 92 , 4 were editorials 93-96 , and 2 were letters to the editor 97,98 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty literature reviews were identified2, 12-30 . Of the remaining studies, 31 presented original research 31-61 , 6 were case series 62-67 , 24 were case reports 68-91 , 1 provided a specialist’s opinion 92 , 4 were editorials 93-96 , and 2 were letters to the editor 97,98 .…”
Section: Resultsmentioning
confidence: 99%
“…A full text review of the remaining 52 studies was then conducted, and 47 records were eliminated since they were reviews, abstract, letters, conferences, without comparison between opioid use and no-opioid use, or without clinical outcomes reported. Therefore, a total of 5 studies with 1,023,224 patients were included in the final analysis [ [22] , [23] , [24] , [25] , [26] ]. The process of study retrieval is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oh et al aimed to investigate whether comorbid musculoskeletal disorders (MSD)s and pain medication use was associated with in-hospital mortality among patients with COVID-19. They found MSDs were not associated with increased in-hospital mortality among patients with COVID-19 19 . Lee et al found potential associations between physical activity and risk of infection, severe illness from COVID-19 and COVID-19 mortality using a nationwide cohort from South Korea 20 .…”
Section: Discussionmentioning
confidence: 95%